PENINGKATAN KARAKTER EMPATI DAN HASIL BELAJAR MATERI PECAHAN SENILAI DENGAN MODEL PEMBELAJARAN PBL SISWA KELAS IV SDK SENGKAN - Carolin Kekeh; Puji Purnomo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the results of interviews, observations, and questionnaires administered to fourth-grade students of SDK Sengkan. The findings indicated that students’ empathy character was generally categorized as low, and learning outcomes on equivalent fractions had not met the school’s Minimum Mastery Criteria (KKTP) of 66.00. Therefore, this research aimed to improve students’ empathy character and learning outcomes through the implementation of the Problem Based Learning (PBL) model in equivalent fraction material. This study employed Classroom Action Research (CAR) involving fourth-grade students of SDK Sengkan in the 2025/2026 academic year. Data were collected through observation, questionnaires, interviews, and tests. Both quantitative and qualitative data analysis techniques were applied. Based on the analysis of the research findings, it can be concluded that: (1) the Problem Based Learning model effectively enhanced students’ empathy character and learning outcomes through five learning phases, namely orientation, organizing students for learning, guiding investigation, presenting data, and analyzing and evaluating the problem-solving process; (2) students’ average empathy character scores improved from 48.46 (low) in the initial condition to 56.84 (fair) in Cycle I and 79.20 (high) in Cycle II. Meanwhile, the average learning outcomes increased from 63.80 in the initial condition to 65.33 in Cycle I and 72.52 in Cycle II; (3) the application of the PBL model was moderately effective, as indicated by an N-gain score of 0.5934 (59.34%) for empathy character and 0.7111 (71.10%) for learning outcomes. Keywords: Empathy character, learning outcomes, Problem Based Learning